Respublikinės mokslinės techninės bibliotekos fondo analizė (rusų k.) - Janulevičienė, Alma (Knygotyra, 1988)
Nowadays, the investigation of the questions of the scientific management of library stocks has gained great urgency (increased in importance). The tasks of increasing the efficiency of the formation and usage of library stocks highlight the necessity for systematic research into their peculiarities and tendencies of development.This article analyzes the peculiarities and tendencies of the development of the stocks of the Republican Scientific-Technical Library of Lithuania's Scientific-Research Institute of Scientific-Technical Information and Technical-Economic Research. The multifaceted research of the stocks should enable the improvement of library processes and information-bibliography services.The research carried out allows for the following conclusions:• The Republican Scientific-Technical Library, by volume of stocks, is the largest library among scientific libraries of the republic. Its stocks total 40.4 percent of the whole stock of the United Republican Information Stock (URIS).• The library is the main library in URIS, which organizes the stocks of special documentation and literature. A peculiarity of the stock is that special technical documentation and literature have predominated in the stock since 1970, totaling approximately 90.1 percent of the entire stock.• The basic stocks are in the Republican Scientific-Technical Library in Vilnius, which total 87.6 percent of the entire stock.• The superextensive growth of the special technical documentation and literature during 1967-1970 is accounted for by the organization of the departments of patents and technical documentation (as per the decision of the Council of Ministers of Lithuania).• At present, the growth of the stock has stabilized. Every year during 1975-1982, the library received an average of 850.2 thousand documents.• The growth of the quantity of the stocks, completion on the whole, and the growth of the stocks of special kinds of scientific-technical literature and documentation may be defined by a mathematical curve, which shows that from a certain moment, the speed of the growth of the volume of the stocks slows down due to limited resources.